Solar Blind UV Light Induced Photo‐Voltage from Transparent Y2O3: Eu‐PMMA Nanocomposite Film. Issue 4 (14th December 2018) - Jia, Hong; Chen, Jun; Li, Qi; Li, Danyang; Liu, Zhongli; Zhao, Jianguo; Ding, Chaoliang; Zhang, Weiying; Yang, Haifeng; Pan, Liuzhan; Feng, Xun; Chen, Zhi; et al.
Abstract : Transparent inorganic‐organic nanocomposite film (Y2 O3 : Eu‐PMMA)W is fabricated for solar blind UV light photo‐voltage response at room temperature. In suggested design, Y2 O3 : Eu nanoparticales with efficient visible luminescence excited under solar blind UV light is incorporated into an Y2 O3 : Eu‐PMMA nanocomposite film coated onto a glass substrate, which converts solar blind UV light to visible light that is absorbed by the Si‐detector. Photo‐voltage response from the thin film Si‐APD detector attached with the inorganic‐organic nanocomposite film demonstrates a prospective application for solar blind UV light detection. Abstract : Y2O3: Eu‐PMMA film is fabricated for solar blind UV light photo‐voltage response. Y2O3: Eu nanoparticales with efficient visible luminescence excited under solar blind UV light is incorporated into an Y2O3: Eu‐PMMA nanocomposite film coated onto a glass substrate, which converts solar blind UV light to visible light that is absorbed by the Si‐detector for Photo‐voltage response.